Case Report: Radiological characteristics and pathological correlation analysis of extranodal Rosai-Dorfman disease of liver - Zheng, Xingxing; Tian, Hongzhe; Li, Wei; Yang, Meihong; Jin, Chenwang; Pang, Yuhui (Frontiers in Oncology, 2025)
BackgroundRosai Dorfman disease (RDD), also known as sinus histiocytosis with extensive lymph node involvement, is a rare histiocytosis with unknown etiology. Liver RDD is relatively rare and is often reported in individual cases. Exploring the imaging and pathological features of extrahepatic Rosai Dorfman disease (RDD) and conducting a comprehensive analysis of reported cases in domestic and foreign literature to enhance understanding of this rare disease.MethodsWe collected data from a patient diagnosed with liver RDD in our hospital. In addition, we searched for liver RDD cases through PubMed and conducted a literature review.ResultsOf the patient data used in this study, 1 patient’s data was obtained from our hospital records and 16 were retrieved from literature. There were 6 males and 11 females aged between 2-72 years, with an average age of 33.55 ± 19.38 years. Four patients presented with isolated liver nodules without the involvement of lymph nodes or extranodal organs, two patients presented with a case that involved extranodal organs but not lymph nodes, two patients presented with a case involving lymph nodes but not extranodal organs, eight patients presented with a case involving both lymph nodes and extranodal organs and lastly one patient presented with a case that did not involve either lymph nodes or extranodal organs. Four of the patients underwent enhanced scanning. The results revealed that 2 of them showed low enhancement, and the other 2 showed no significant enhancement. Only 1 case underwent PET-CT, and the results indicated a high uptake. Immunohistochemistry was performed on all 17 cases of liver RDD, and the results were positive for CD1a (-), CD68 (+), and S-100 (+).ConclusionsLiver RDD can manifest at any age. It presents with nonspecific imaging findings and a challenging preoperative diagnosis. Patients with extranodal hepatic RDD present with typical RDD characteristic immunohistochemistry features such as, high uptake on PET-CT, and no to mild enhancement on contrast-enhanced scans. For an early diagnosis, it is beneficial to fully comprehend these traits.